Differences in drug availability levels before and during the covid19 pandemic in the pharmaceutical installation of NTB provincial hospital - Wisnu, M. Ari; Herowati, Rina; Harsono, Samuel Budi (Journal of Health Management and Pharmacy Exploration, 2024)
Health services are now increasingly needed during the COVID-19 pandemic which threatens public health. The need for public medicines that must be available such as flu, cough, vitamin c, antibiotics and antimalarials and antivirals for health services makes hospitals must try to fulfil and currently the COVID-19 pandemic situation is still continuing so hospitals must be ready to provide health services to patients.This study aims to determine the differences in drugs in the Pharmacy Installation of the NTB Provincial Hospital before the COVID-19 pandemic in 2019 and during the COVID-19 pandemic in 2020. This study is a descriptive-evaluative study with retrospective data collection in 2019 which represents the period before the COVID-19 pandemic and 2020 which represents the COVID-19 pandemic. The samples used in the study consisted of drug data from the Pharmacy Installation of the NTB Province Regional General Hospital (RSUD) and were analyzed using the Wilcoxon test. The results obtained are the level of drug availability in the pharmaceutical installation of the NTB Provincial Hospital obtained based on the results of observing data in 2019 and 2020, namely 19 and 37 months. There is a significant difference (Asymp. Sig (2-tailed) 0.000) the level of drug availability in the Pharmacy Installation of the NTB Provincial Hospital before and during the COVID-19 pandemic in 2020 with a difference of 18 months.